Catalyst composition for catalyzing fischer-tropsch reaction
Patent Information
- Application Number
- JP2024034879
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-13
- Filing Date
- 2024-03-07
- Publication Date
- 2025-03-26
AI Technical Summary
【0007】 本発明によれば、フィッシャー·トロプシュ反応を触媒する触媒組成物であって、触媒活性の低下が抑制された触媒組成物が提供される。
Smart Images

Figure 2025041503000001 
Figure 2025041503000002 
Figure 2025041503000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a catalyst composition for catalyzing the Fischer-Tropsch reaction. [Background technology]
[0002] In recent years, due to the tightening of environmental regulations and the growing environmental awareness on a global scale, alternative energy sources to replace petroleum resources have been attracting attention, and interest in the Fischer-Tropsch reaction, which is a reaction for synthesizing hydrocarbons from synthesis gas (CO and H2), has been increasing. Patent Document 1 discloses a catalyst for the Fischer-Tropsch reaction in which a metal selected from iron, cobalt, nickel, and ruthenium is supported on a support having a specific average pore size. Patent Document 2 discloses a Fischer-Tropsch reaction process using a catalyst in which iron-containing particles are dispersed on an α-alumina support. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2003-24786 A [Patent Document 2] Special Publication No. 2013-509353 Summary of the Invention [Problem to be solved by the invention]
[0004] The present inventors have studied conventional catalyst compositions for the Fischer-Tropsch reaction and found that the catalytic activity of the catalyst composition decreases while the catalyst composition is used in the Fischer-Tropsch reaction. The present inventors believe that sintering of metals that occurs when metal oxides in the catalyst composition are reduced by reducing gases such as H2 in the feed gas and CO generated in the reaction system is one of the causes of the decrease in the specific surface area of the catalyst composition (i.e., the reaction active sites of the catalyst composition), and that the decrease in the specific surface area of the catalyst composition is one of the causes of the decrease in the catalytic activity of the catalyst composition. However, the cause of the decrease in the catalytic activity of the catalyst composition is not limited to the decrease in the specific surface area of the catalyst composition.
[0005] Therefore, an object of the present invention is to provide a catalyst composition for catalyzing a Fischer-Tropsch reaction, in which a decrease in catalytic activity is suppressed. [Means for solving the problem]
[0006] In order to solve the above problems, the present invention provides the following catalyst composition. [1] A catalyst composition for catalyzing a Fischer-Tropsch reaction, comprising: Ingredients include: (a) one or more components selected from oxides of Group 8 elements, oxides of Group 9 elements, and oxides of Group 10 elements; (b) one or more components selected from oxides and hydrates thereof of Group 3 elements, oxides and hydrates thereof of Group 4 elements, oxides and hydrates thereof of Group 5 elements, oxides and hydrates thereof of Group 6 elements, oxides and hydrates thereof of Group 13 elements, and oxides and hydrates thereof of Group 14 elements; and (c) one or more components selected from the group consisting of oxides, carbonates, and nitrates of Group 1 elements and oxides, carbonates, and nitrates of Group 2 elements; Including, A catalyst composition, wherein the crystallite size of the component (b) is 5.0 nm or more and 90.0 nm or less. [2] The catalyst composition according to [1], which catalyzes a reverse water gas shift reaction. [3] The catalyst composition according to [1] or [2], wherein the crystallite size of the component (a) is 200.0 nm or less. [4] The catalyst composition according to any one of [1] to [3], wherein the content of the component (b) is 1.0 mass % or more and 50.0 mass % or less, based on the mass of the catalyst composition. [5] The catalyst composition according to any one of [1] to [4], wherein the content of the component (a) is 30.0 mass % or more and 98.0 mass % or less, based on the mass of the catalyst composition. [6] The catalyst composition according to any one of [1] to [5], wherein the content of the component (c) is 0.1 mass % or more based on the mass of the catalyst composition. [7] The catalyst composition according to any one of [1] to [6], wherein the component (b) contains one or more elements selected from Al, Zr and Si. [8] The catalyst composition according to any one of [1] to [7], wherein the component (b) comprises one or more selected from boehmite, γ-Al2O3, and θ-Al2O3. Effect of the Invention
[0007] According to the present invention, there is provided a catalyst composition for catalyzing a Fischer-Tropsch reaction, in which a decrease in catalytic activity is suppressed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] ≪Catalyst composition≫ The catalyst composition of the present invention will now be described.
[0009] The present invention relates to a catalyst composition that catalyzes the Fischer-Tropsch reaction (hereinafter referred to as the "FT reaction").
[0010] The FT reaction is a reaction that synthesizes hydrocarbons from synthesis gas (CO and H2) and is represented by the following reaction formula. nCO + 2nH2 → -(CH2) n - + nH2O
[0011] The catalyst composition of the present invention preferably catalyzes the reverse water gas shift reaction (hereinafter referred to as "RWGS reaction") in addition to the FT reaction.
[0012] The RWGS reaction is a reaction in which CO2 reacts with H2 to convert it into CO, and is represented by the following reaction formula: CO2+ H2→ CO + H2O
[0013] The CO obtained by the RWGS reaction can be used as a raw material gas for the FT reaction. Therefore, when the catalyst composition of the present invention catalyzes the RWGS reaction in addition to the FT reaction, the catalyst composition of the present invention can be used as a catalyst for a series of reactions including the RWGS reaction and the FT reaction carried out using the CO obtained by the RWGS reaction as a raw material gas.
[0014] The catalyst composition of the present invention is, for example, in the form of a powder. The catalyst composition of the present invention may be formed into a desired shape such as pellets or a layer.
[0015] The catalyst composition of the present invention is characterized in that it contains components (a) to (c), and the crystallite size of component (b) is 5 nm or more and 90 nm or less. This makes it possible to suppress the decrease in the catalytic activity of the catalyst composition. Since component (b) is present between components (a) and can form gaps, it is possible to suppress the decrease in the specific surface area of the catalyst composition (i.e., the reaction active points of the catalyst composition) caused by sintering of components (a) that may occur during the use of the catalyst composition in a desired reaction (FT reaction, or a series of reactions including RWGS reaction and FT reaction). The present inventor believes that the suppression of the decrease in the specific surface area of the catalyst composition is one of the factors that suppress the decrease in the catalytic activity of the catalyst composition. However, the factor that suppresses the decrease in the catalytic activity of the catalyst composition is not limited to the suppression of the decrease in the specific surface area of the catalyst composition.
[0016] The catalyst composition of the present invention may contain a component (d) in addition to the components (a) to (c).
[0017] The component (a) will be described below.
[0018] Component (a) is composed of one or more elements selected from the group consisting of oxides of Group 8 elements, oxides of Group 9 elements, and oxides of Group 10 elements. That is, component (a) contains one or more metal elements selected from the group consisting of elements of Group 8 elements, elements of Group 9 elements, and elements of Group 10, and the various metal elements are present in the form of oxides.
[0019] Component (a) is converted to a metal by reduction with H2. The metal produced by the reduction of component (a) reacts with the raw material gas to form a catalytically active component (carbide and / or oxide), forming a site that plays a central role in the FT reaction and the RWGS reaction. The catalytically active component contributes to the adsorption and dissociation of the raw material gas (CO2, CO, H2), activation of the reaction intermediate on the surface of the catalyst composition, stabilization of the reaction intermediate held on the surface of the catalyst composition, etc. The stabilization of the reaction intermediate held on the surface of the catalyst composition involves the bond (e.g., Fe-C bond) between the catalytically active component and the reaction intermediate.
[0020] In one embodiment, component (a) is reduced with H in the feed gas during use of the catalyst composition in the desired reaction. In another embodiment, component (a) is reduced by a reduction treatment carried out prior to use of the catalyst composition in the desired reaction.
[0021] Component (a) is, for example, in particulate form.
[0022] When component (a) is composed of two or more components, component (a) may be a mixture of two or more components or a complex of two or more components. In this specification, "a mixture of two or more components" means a state in which the two or more components exist independently, and "a complex of two or more components" means a state in which the two or more components are chemically bonded. A complex of two or more components also includes a solid solution of the two or more components.
[0023] The group 8 elements include Fe, Ru, and Os. Therefore, the oxides of the group 8 elements include Fe oxides (one or more selected from Fe2O3, Fe3O4, and FeO), Ru oxides (RuO2), and Os oxides (OsO4). From the viewpoint of promoting the reaction through the promotion of the adsorption and dissociation of the raw material gas, the oxides of the group 8 elements are preferably selected from Fe oxides and Ru oxides, and more preferably Fe oxides.
[0024] The group 9 elements include Co, Rh, and Ir. Therefore, the oxides of the group 9 elements include Co oxide (Co3O4), Rh oxide (RhO2), and Ir oxide (one or two selected from IrO2 and Ir2O3). From the viewpoint of promoting the reaction through the promotion of the adsorption and dissociation of the raw material gas, the oxide of the group 9 element is preferably Co oxide.
[0025] Group 10 elements include Ni, Pd, and Pt. Therefore, the oxides of Group 10 elements include Ni oxide (NiO), Pd oxide (PdO), and Pt oxide (PtO2). From the viewpoint of promoting the reaction through the promotion of the adsorption and dissociation of the raw material gas, the oxide of Group 10 element is preferably Ni oxide.
[0026] From the viewpoint of catalyzing both the RWGS reaction and the FT reaction, component (a) preferably contains one or more oxides selected from Fe oxide, Co oxide, and Ni oxide, and more preferably contains Fe oxide.
[0027] From the viewpoint of increasing the specific surface area of the catalyst composition (i.e., the reaction active points of the catalyst composition), the crystallite diameter of the component (a) is preferably 200.0 nm or less, more preferably 100.0 nm or less, and even more preferably 50.0 nm or less. Assuming that the shape of the component (a) is a perfect sphere, there is a negative correlation between the crystallite diameter of the component (a) and the specific surface area of the component (a), so the smaller the crystallite diameter of the component (a), the larger the specific surface area of the component (a). That is, the smaller the crystallite diameter of the component (a), the more reaction active points originating from the component (a) in the catalyst composition. The lower limit of the crystallite diameter of the component (a) is not particularly limited, but from the viewpoint of improving the handleability during the preparation of the catalyst composition, it may be, for example, 5.0 nm or more, 10.0 nm or more, or 20.0 nm or more. Each of these lower limits may be combined with any of the above-mentioned upper limits.
[0028] When component (a) is composed of one component, the crystallite size of the one component is preferably within the above range. When component (a) is composed of two or more components, the crystallite size of at least one component is preferably within the above range, and the crystallite sizes of all components are more preferably within the above range.
[0029] When component (a) is composed of Fe oxide, the crystallite size of the Fe oxide is preferably within the above range. When component (a) contains Fe oxide and one or more other components, the crystallite size of at least the Fe oxide is preferably within the above range, and it is more preferable that the crystallite sizes of all the components are within the above range.
[0030] The method for measuring the crystallite size of component (a) is as follows. X-ray diffraction (XRD) is performed using a sample obtained from the catalyst composition of the present invention and a commercially available X-ray diffractometer, and a peak derived from component (a) is identified in the obtained XRD pattern. The Scherrer formula is as follows. The Scherrer constant is 0.94. D=K×λ / Bcosθ [In the formula, D represents the crystallite size (nm), K represents the Scherrer constant, λ represents the wavelength of X-rays (nm), B represents the broadening of the diffraction line width (rad), and θ represents the Bragg angle (rad).]
[0031] For Fe2O3, the crystallite diameter obtained from the peak at 2θ=35.6°±0.5° is regarded as the crystallite diameter of Fe2O3.
[0032] For Fe3O4, the crystallite diameter obtained from the peak at 2θ=35.5°±0.5° is regarded as the crystallite diameter of Fe3O4.
[0033] For FeO, the crystallite diameter obtained from the peak at 2θ=41.4°±0.5° is regarded as the crystallite diameter of FeO.
[0034] For Co3O4, the crystallite diameter obtained from the peak at 2θ=37.0°±0.5° is regarded as the crystallite diameter of Co3O4.
[0035] For NiO, the crystallite diameter obtained from the peak at 2θ=43.0°±0.5° is regarded as the crystallite diameter of NiO.
[0036] For oxides of other Group 8 elements, Group 9 elements, and Group 10 elements, the peak with the highest intensity is determined from the XRD pattern that can be confirmed using the ICSD (Inorganic Crystal Structure Database) provided by the Chemical Information Association, and the crystallite size determined from that peak is used as the crystallite size of the oxides of other Group 8 elements, Group 9 elements, and Group 10 elements.
[0037] The crystallite size of component (a) can be adjusted, for example, when the catalyst composition is prepared by a precipitation method, by adjusting the rate at which the precipitate forms or by increasing the temperature at which the precipitate is calcined.
[0038] From the viewpoint of increasing the amount of catalytically active components, the content of component (a) is preferably 30.0 mass% or more and 98.0 mass% or less, more preferably 50.0 mass% or more and 98.0 mass% or less, and even more preferably 70.0 mass% or more and 98.0 mass% or less, based on the mass of the catalyst composition of the present invention. When component (a) is composed of two or more components, the "content of component (a)" means the total content of the two or more components.
[0039] The content of component (a) can be measured using X-ray fluorescence analysis (XRF). XRF can be performed according to the conditions described in the Examples. XRF determines the oxide-equivalent contents of various metal elements. For Fe, the Fe2O3-equivalent content is taken as the Fe oxide-equivalent content. For Ir, the Ir2O3-equivalent content is taken as the Ir oxide-equivalent content.
[0040] The component (b) will be described below.
[0041] Component (b) is composed of one or more selected from the group 3 element oxides and their hydrates, the group 4 element oxides and their hydrates, the group 5 element oxides and their hydrates, the group 6 element oxides and their hydrates, the group 13 element oxides and their hydrates, and the group 14 element oxides and their hydrates. That is, component (b) contains one or more metal elements selected from the group 3 elements, the group 4 elements, the group 5 elements, the group 6 elements, the group 13 elements, and the group 14 elements, and each metal element exists in the form of an oxide and / or an oxide hydrate. It is preferable that at least a part of each metal element exists in the form of an oxide. The metal elements also include metalloid elements such as Si and B.
[0042] In the phrase "selected from oxides and hydrates of Group 3 elements, oxides and hydrates of Group 4 elements, oxides and hydrates of Group 5 elements, oxides and hydrates of Group 6 elements, oxides and hydrates of Group 13 elements, and oxides and hydrates of Group 14 elements," "oxides and hydrates of Group 3 elements" means that the oxides of Group 3 elements and the hydrates of oxides of Group 3 elements are each options for component (b). Therefore, either the oxides of Group 3 elements or the hydrates of oxides of Group 3 elements may be selected as component (b), or both the oxides of Group 3 elements and the hydrates of oxides of Group 3 elements may be selected as component (b). The same applies to "oxides and hydrates of Group 4 elements," "oxides and hydrates of Group 5 elements," "oxides and hydrates of Group 6 elements," "oxides and hydrates of Group 13 elements," and "oxides and hydrates of Group 14 elements."
[0043] Component (b) is a component that is responsible for maintaining the structure of the catalyst composition. Component (b) maintains the specific surface area of the catalyst composition, thereby contributing to an improvement in the CO2 conversion rate.
[0044] Component (b) is, for example, in particulate form.
[0045] When component (b) is composed of two or more components, component (b) may be a mixture of two or more components or a complex of two or more components. The meaning of "complex" is as described above.
[0046] Group 3 elements are Sc, Y, and lanthanides ( 57 La~ 71 Lu) and actinides. Thus, the oxides and hydrates of Group 3 elements include Sc oxide (Sc2O3) and hydrates thereof, Y oxide (Y2O3) and hydrates thereof, lanthanide oxides and hydrates thereof, and actinide oxides and hydrates thereof. In this specification, actinides are defined as: 89 Ac~ 99The oxides of rare earth elements other than Ce, Pr, and Tb are called sesquioxides, M2O3 (where M represents a rare earth element other than Ce, Pr, and Tb), Ce oxides are called CeO2, and Pr oxides are called Pr6O 11 , the Tb oxide is Tb4O7. The actinide oxide excluding U oxide is M2O3 (M represents an actinide element excluding U), and the U oxide is UO3. From the viewpoints of ease of use from the standpoints of cost and safety, of mature nanoparticle production technology, and of ease of exerting the effect of component (b), the oxide and hydrate thereof of the Group 3 element are preferably selected from La oxide and hydrate thereof, and Ce oxide and hydrate thereof.
[0047] The Group 4 elements include Ti, Zr, and Hf. Therefore, the oxides and hydrates of the Group 4 elements include Ti oxide (TiO2) and hydrates thereof, Zr oxide (ZrO2) and hydrates thereof, and Hf oxide (HfO2) and hydrates thereof. From the viewpoint that nanoparticle production technology is mature and the effect of component (b) can be easily exerted, it is preferable that the oxides and hydrates of the Group 4 elements are selected from Ti oxide and hydrates thereof, and Zr oxide and hydrates thereof.
[0048] Group 5 elements include V, Nb, and Ta. Thus, the oxides and hydrates of Group 5 elements include V oxide (V2O3) and hydrates thereof, Nb oxide (Nb2O5) and hydrates thereof, and Ta oxide (Ta2O5) and hydrates thereof. From the viewpoint that nanoparticle production technology is mature and the effect of component (b) can be easily exerted, it is preferable that the oxides and hydrates of Group 5 elements are selected from Ta oxide and hydrates thereof.
[0049] The Group 6 elements include Cr, Mo, and W. Thus, the oxides and hydrates of the Group 6 elements include Cr oxide (Cr2O3) and hydrates thereof, Mo oxide (one or two selected from MoO2 and MoO3) and hydrates thereof, and W oxide (WO3) and hydrates thereof. From the viewpoint that nanoparticle production technology is mature and the effect of component (b) can be easily exerted, it is preferable that the oxides and hydrates of the Group 6 elements are selected from Cr oxide and hydrates thereof.
[0050] The group 13 elements include B, Al, Ga, In, and Tl. Therefore, the oxides and hydrates of the group 13 elements include B oxide (B2O3) and hydrates thereof, Al oxide (Al2O3) and hydrates thereof, Ga oxide (Ga2O3) and hydrates thereof, In oxide (In2O3) and hydrates thereof, and Tl oxide (Tl2O3) and hydrates thereof. From the viewpoint that nanoparticle production technology is mature and the effect of component (b) can be easily exerted, the oxides and hydrates of the group 13 elements are preferably selected from B oxide and hydrates thereof, and Al oxide and hydrates thereof, and more preferably selected from Al oxide and hydrates thereof.
[0051] The group 14 elements include Si, Ge, Sn, and Pb. Therefore, the oxides and hydrates of the group 14 elements include Si oxide (SiO2) and hydrates thereof, Ge oxide (GeO2) and hydrates thereof, Sn oxide (SnO2) and hydrates thereof, and Pb oxide (one or two selected from PbO and PbO2) and hydrates thereof. From the viewpoints of high stability under a reducing atmosphere, mature technology for producing nanoparticles, and ease of exerting the effect of component (b), the oxides and hydrates of the group 14 elements are preferably selected from Si oxide and hydrates thereof.
[0052] From the viewpoint that component (b) has a strong interaction with component (a) and easily forms a contact point with component (a), and is present between components (a) to easily suppress sintering of components (a), component (b) preferably contains one or more elements selected from Al, Zr, and Si, and more preferably contains one or two elements selected from Al and Si. That is, component (b) preferably contains one or more elements selected from Al oxide and its hydrate, Zr oxide and its hydrate, and Si oxide and its hydrate, and more preferably contains one or more elements selected from Al oxide and its hydrate, and Si oxide and its hydrate. The embodiment in which component (b) contains one or more selected from Al oxide and its hydrate, and Si oxide and its hydrate includes an embodiment in which component (b) contains Si oxide and / or its hydrate and does not contain either Al oxide or its hydrate, an embodiment in which component (b) contains Al oxide and / or its hydrate and does not contain Si oxide or its hydrate, and an embodiment in which component (b) contains Si oxide and / or its hydrate and Al oxide and / or its hydrate. Component (b) may be composed of one or more selected from Al oxide and its hydrate, and Si oxide and its hydrate, or may contain one or more other components in addition to one or more selected from Al oxide and its hydrate, and Si oxide and its hydrate.
[0053] As long as the crystallite size is 5.0 nm or more and 90.0 nm or less, the Al oxide may be any of α-Al2O3, γ-Al2O3, θ-Al2O3, ε-Al2O3, κ-Al2O3, η-Al2O3, χ-Al2O3, or ρ-Al2O3. The Al oxide may be composed of one type selected from these, or may be composed of two or more types selected from these. From the viewpoint of enhancing the effect of component (b), it is preferable that the Al oxide contains one or two or more types selected from γ-Al2O3 and θ-Al2O3.
[0054] Examples of the hydrates of Al oxide include alumina monohydrate and alumina trihydrate.
[0055] Examples of alumina monohydrate include boehmite (α-AlOOH), diaspore (β-AlOOH), etc. The boehmite may be so-called pseudo-boehmite, which contains one or more water molecules between layers.
[0056] Examples of alumina trihydrate include gibbsite (α-Al(OH)3) and bayerite (β-Al(OH)3).
[0057] From the viewpoint of enhancing the effect of the component (b), the hydrate of Al oxide is preferably alumina monohydrate, more preferably boehmite.
[0058] From the viewpoint of enhancing the effect of the component (b), the component (b) preferably contains one or more selected from boehmite, γ-Al2O3, and θ-Al2O3.
[0059] The crystallite size of component (b) is 5.0 nm or more and 90.0 nm or less. This can suppress the decrease in catalytic activity of the catalyst composition. Since component (b) is present between components (a) and can form gaps, it is possible to suppress the decrease in the specific surface area of the catalyst composition (i.e., the reaction active points of the catalyst composition) caused by sintering of components (a) that may occur during the use of the catalyst composition in a desired reaction (FT reaction, or a series of reactions including RWGS reaction and FT reaction). The present inventor believes that the suppression of the decrease in the specific surface area of the catalyst composition is one of the factors that suppress the decrease in the catalytic activity of the catalyst composition. However, the factor of the suppression of the decrease in the catalytic activity of the catalyst composition is not limited to the suppression of the decrease in the specific surface area of the catalyst composition. From the viewpoint of more effectively suppressing the decrease in the catalytic activity of the catalyst composition, the crystallite size of component (b) is preferably 5.0 nm or more and 70.0 nm or less, more preferably 5.0 nm or more and 40.0 nm or less, and even more preferably 5.0 nm or more and 10.0 nm or less.
[0060] When component (b) is composed of one component, the crystallite size of the one component is within the above range. When component (b) is composed of two or more components, the crystallite size of at least one component may be within the above range, but it is preferable that the crystallite sizes of all components are within the above range.
[0061] When component (b) is composed of one or more selected from Al oxide and its hydrate, Zr oxide and its hydrate, and Si oxide and its hydrate, the crystallite diameter of at least one component may be within the above range, but it is preferable that the crystallite diameter of all components is within the above range. When component (b) contains one or more selected from Al oxide and its hydrate, Zr oxide and its hydrate, and Si oxide and its hydrate, as well as one or more other components, the crystallite diameter of at least one or more selected from Al oxide and its hydrate, Zr oxide and its hydrate, and Si oxide and its hydrate may be within the above range, but it is preferable that the crystallite diameter of all components is within the above range.
[0062] The method for measuring the crystallite size of component (b) is the same as the method for measuring the crystallite size of component (a).
[0063] For α-Al2O3, the crystallite diameter obtained from the peak at 2θ=43.0°±0.5° is regarded as the crystallite diameter of α-Al2O3.
[0064] For γ-Al2O3, the crystallite diameter obtained from the peak present at 2θ=45.0°±0.5° is regarded as the crystallite diameter of γ-Al2O3.
[0065] Regarding θ-Al2O3, the crystallite diameter obtained from the peak present at 2θ=45.0°±0.5° is regarded as the crystallite diameter of θ-Al2O3.
[0066] For ε-Al2O3, the crystallite diameter obtained from the peak at 2θ=45.9°±0.5° is regarded as the crystallite diameter of ε-Al2O3.
[0067] For κ-Al2O3, the crystallite diameter obtained from the peak at 2θ=67.3°±0.5° is regarded as the crystallite diameter of κ-Al2O3.
[0068] For η-Al2O3, the crystallite diameter obtained from the peak at 2θ=66.8°±0.5° is regarded as the crystallite diameter of η-Al2O3.
[0069] For χ-Al2O3, the crystallite diameter obtained from the peak at 2θ=67.2°±0.5° is regarded as the crystallite diameter of χ-Al2O3.
[0070] For ρ-Al2O3, the crystallite diameter obtained from the peak at 2θ=13.9°±0.5° is regarded as the crystallite diameter of ρ-Al2O3.
[0071] For boehmite, the crystallite diameter determined from the peak present at 2θ=14.5°±0.5° is regarded as the crystallite diameter of boehmite.
[0072] For diaspore, the crystallite diameter determined from the peak present at 2θ=22.5°±0.5° is regarded as the crystallite diameter of diaspore.
[0073] For gibbsite, the crystallite diameter determined from the peak present at 2θ=18.3°±0.5° is regarded as the crystallite diameter of gibbsite.
[0074] For bayerite, the crystallite diameter determined from the peak present at 2θ=18.7°±0.5° is regarded as the crystallite diameter of bayerite.
[0075] For ZrO2, the crystallite diameter obtained from the peak at 2θ=30.3±0.5° is regarded as the crystallite diameter of ZrO2.
[0076] For SiO2, the crystallite diameter obtained from the peak at 2θ=26.4±0.5° is regarded as the crystallite diameter of SiO2.
[0077] For oxides of other Group 3 elements, Group 4 elements, Group 5 elements, Group 6 elements, Group 13 elements, and Group 14 elements, the peak with the highest intensity is obtained from the XRD pattern that can be confirmed by ICSD (Inorganic Crystal Structure Database) provided by the Chemical Information Association, and the crystallite size obtained from the peak is the crystallite size of the oxides of other Group 3 elements, Group 4 elements, Group 5 elements, Group 6 elements, Group 13 elements, and Group 14 elements. The crystallite size can also be measured in the same manner for hydrates of oxides of other Group 3 elements, Group 4 elements, Group 5 elements, Group 6 elements, Group 13 elements, and Group 14 elements.
[0078] The crystallite size of component (b) can be adjusted by controlling the preparation conditions of the oxide or its hydrate. For example, Al2O3 is generally obtained by hydrolysis of alumina alkoxide, and by appropriately controlling the conditions during hydrolysis and the subsequent heat treatment conditions, it is possible to synthesize an Al oxide or its hydrate having a desired crystallite size.
[0079] In order to more effectively suppress the decrease in the catalytic activity of the catalyst composition, the median diameter D 50 is preferably 0.050 μm or more and 40.0 μm or less, more preferably 0.050 μm or more and 30.0 μm or less, and even more preferably 0.050 μm or more and 20.0 μm or less. 50 does not change significantly before and after the preparation of the catalyst composition, so the median diameter D 50 It is preferable that the raw material for component (b) is described later.
[0080] When component (b) is composed of one component, the median diameter D of the one component 50 In the case where component (b) is composed of two or more components, the median diameter D of at least one of the components is preferably in the above range. 50 is preferably in the above range, and the median diameter D 50 It is more preferable that the above range.
[0081] When component (b) is composed of one or more selected from Al oxide and its hydrate, Zr oxide and its hydrate, and Si oxide and its hydrate, the median diameter D of at least one component 50 is preferably in the above range, and the median diameter D 50 It is more preferable that the above range.
[0082] Median diameter D 50 is the particle size at which the cumulative volume is 50% in the volume-based particle size distribution measured by a laser diffraction scattering particle size distribution measurement method. 50 does not change significantly before and after the preparation of the catalyst composition, so the median diameter D 50 is the median diameter D of the component (b) in the catalyst composition. 50 The median diameter D of the raw material of component (b) can be considered as 50 can be measured after dispersing the raw material of component (b) in water, using a particle size distribution measuring device according to the conditions described in the examples.
[0083] Component (b) preferably has a strong interaction with component (a) or a catalytically active component derived from component (a), while it is likely to form a difficult-to-reduc compound at the interface with component (a) or a catalytically active component derived from component (a). Therefore, the content of component (b) is preferably 1.0 mass% or more and 50.0 mass% or less, more preferably 1.0 mass% or more and 30.0 mass% or less, and even more preferably 1.0 mass% or more and 25.0 mass% or less, based on the mass of the catalyst composition of the present invention. When the content of component (b) is within the above range, the generation of a difficult-to-reduc compound can be suppressed, and component (b) in the catalyst composition can be effectively utilized. When component (b) is composed of two or more components, the "content of component (b)" means the total content of the two or more components.
[0084] From the viewpoint of effectively allowing component (b) to be present in the gaps between components (a), the ratio of the content of component (b) to the content of component (a) is preferably 0.01 or more and 0.5 or less, more preferably 0.01 or more and 0.3 or less, and even more preferably 0.01 or more and 0.25 or less.
[0085] The content of component (b) can be measured using X-ray fluorescence analysis (XRF). XRF can be performed according to the conditions described in the Examples. XRF determines the contents of various metal elements in terms of their oxides. For Mo, the content of Mo in terms of MoO3 is taken as the content of Mo in terms of its oxides. For Pb, the content of Pb in terms of PbO is taken as the content of Pb in terms of its oxides.
[0086] The component (c) will be described below.
[0087] Component (c) is composed of one or more selected from oxides, carbonates, and nitrates of Group 1 elements and oxides, carbonates, and nitrates of Group 2 elements. That is, component (c) contains one or more selected from Group 1 elements and Group 2 elements, and various metal elements exist in one or more states selected from oxides, carbonates, and nitrates. At least a part of various metal elements preferably exists in one or two states selected from oxides and carbonates, and more preferably exists in the oxide state. Metalloid elements such as Be are also included in the metal elements.
[0088] In the phrase "selected from oxides, carbonates, and nitrates of Group 1 elements, and oxides, carbonates, and nitrates of Group 2 elements," "oxides, carbonates, and nitrates of Group 1 elements" means that oxides of Group 1 elements, carbonates of Group 1 elements, and nitrates of Group 1 elements are each options for component (c). Therefore, one or more of the oxides, carbonates, and nitrates of Group 1 elements may be selected. The same applies to "oxides, carbonates, and nitrates of Group 2 elements."
[0089] Component (c) is a promoter component that contributes to enhancing the adsorption of raw material gases (CO2, CO, H2), promoting the production of reaction intermediates by donating electrons to the catalytically active components, catalytic activity of the FT reaction, and stabilizing the bond between the catalytically active components and reaction intermediates by donating electrons to the catalytically active components (stabilizing the reaction intermediates held on the surface of the catalyst composition through the bond between the catalytically active components and reaction intermediates).
[0090] Component (c) is, for example, in particulate form.
[0091] When component (c) is composed of two or more components, component (c) may be a mixture of two or more components or a complex of two or more components. The meaning of "complex" is as described above.
[0092] Group 1 elements include Li, Na, K, Rb, Cs, and Fr. Thus, oxides of Group 1 elements include Li oxide (Li2O), Na oxide (Na2O), K oxide (K2O), Rb oxide (Rb2O), Cs oxide (Cs2O), and Fr oxide (Fr2O). Carbonates of Group 1 elements include Li carbonate (Li2CO3), Na carbonate (Na2CO3), K carbonate (K2CO3), Rb carbonate (Rb2CO3), Cs carbonate (Cs2CO3), and Fr carbonate (Fr2CO3). Nitrates of Group 1 elements include Li nitrate (LiNO3), Na nitrate (NaNO3), K nitrate (KNO3), Rb nitrate (RbNO3), Cs nitrate (CsNO3), and Fr nitrate (FrNO3). From the viewpoint of enhancing the effect of component (c), the oxide, carbonate and nitrate of the Group 1 element are preferably selected from Na oxide, Na carbonate and Na nitrate, more preferably Na oxide and Na carbonate, and more preferably Na oxide.
[0093] Group 2 elements include Be, Mg, Ca, Sr, Ba, and Ra. Thus, oxides of Group 2 elements include Be oxide (BeO), Mg oxide (MgO), Ca oxide (CaO), Sr oxide (SrO), Ba oxide (BaO), and Ra oxide (RaO). Carbonates of Group 2 elements include Be carbonate (BeCO3), Mg carbonate (MgCO3), Ca carbonate (CaCO3), Sr carbonate (SrCO3), Ba carbonate (BaCO3), and Ra carbonate (RaCO3). Nitrates of Group 2 elements include Be nitrate (Be(NO3)2), Mg nitrate (Mg(NO3)2), Ca nitrate (Ca(NO3)2), Sr nitrate (Sr(NO3)2), Ba nitrate (Ba(NO3)2), and Ra nitrate (Ra(NO3)2). From the viewpoint of enhancing the effect of component (c), the oxide, carbonate and nitrate of the Group 2 element are preferably selected from Mg oxide, Mg carbonate, Mg nitrate, Ca oxide, Ca carbonate and Ca nitrate, and more preferably selected from Mg oxide, Mg carbonate, Ca oxide and Ca carbonate.
[0094] From the viewpoint of enhancing the effect of component (c), component (c) preferably contains one or more types selected from Na oxide, Na carbonate, and Na nitrate, and more preferably contains one or two types selected from Na oxide and Na carbonate.
[0095] From the viewpoint of enhancing the action of component (c), the content of component (c) is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, and even more preferably 0.5 mass% or more, based on the mass of the catalyst composition of the present invention. The upper limit is not particularly limited. The content of component (c) may be, for example, 20.0 mass% or less, 10.0 mass% or less, or 5.0 mass% or less. Each of these upper limits may be combined with any of the above-mentioned lower limits. When component (c) is composed of two or more components, the "content of component (c)" means the total content of the two or more components.
[0096] The greater the number of contacts between component (a) and component (c), the greater the effect of component (c). The number of contacts between component (a) and component (c) is determined by the ratio of the content of component (c) to the content of component (a). From the viewpoint of enhancing the effect of component (c), the ratio of the content of component (c) to the content of component (a) is preferably 0.01 or more. The upper limit is not particularly limited. The ratio may be, for example, 0.1 or less. This upper limit may be combined with the above-mentioned lower limit.
[0097] The content of component (c) can be measured using X-ray fluorescence spectrometry (XRF). XRF can be performed according to the conditions described in the Examples. XRF determines the content of various metal elements in terms of oxides. For example, for Na, the content of Na in terms of Na2O is determined.
[0098] It is preferable that components (a) to (c) form a mixture. The mixture of components (a) to (c) is, for example, a mixed particle containing particles of component (a), particles of component (b), and particles of component (c). Furthermore, components (a) and (c) may form a complex. The meaning of "complex" is as described above.
[0099] The component (d) will be described below.
[0100] Component (d) is composed of one or more elements selected from oxides and hydrates thereof of elements of Group 11. That is, component (d) contains one or more metal elements selected from elements of Group 11, and each metal element exists in the form of an oxide and / or an oxide hydrate. It is preferable that at least a part of each metal element exists in the form of an oxide.
[0101] Component (d) is a component that enhances the action of component (c). In particular, component (d) enhances the electron donating effect from component (c) to the catalytically active component by promoting the reduction of component (c), and contributes to stabilization of the bond between the catalytically active component and the reaction intermediate (stabilization of the reaction intermediate held on the surface of the catalyst composition through the bond between the catalytically active component and the reaction intermediate).
[0102] Component (d) is, for example, in particulate form.
[0103] When component (d) is composed of two or more components, component (d) may be a mixture of two or more components or a complex of two or more components. The meaning of "complex" is as described above.
[0104] The group 11 elements include Cu, Ag, and Au. Therefore, the oxides and hydrates of the group 11 elements include Cu oxides (one or two selected from Cu2O and CuO) and hydrates thereof, Ag oxides (Ag2O) and hydrates thereof, and Au oxides (Au2O3) and hydrates thereof. From the viewpoint of enhancing the effect of component (c), the oxides and hydrates of the group 11 elements are preferably selected from Cu oxides and hydrates thereof, and Ag oxides and hydrates thereof.
[0105] From the viewpoint of enhancing the effect of component (d), the content of component (d) is preferably 1 mass% or more and 20 mass% or less, more preferably 2 mass% or more and 15 mass% or less, and even more preferably 2.5 mass% or more and 12 mass% or less, based on the mass of the catalyst composition of the present invention. When component (d) is composed of two or more components, the "content of component (d)" means the total content of the two or more components.
[0106] The greater the number of contacts between component (d) and component (c), the greater the effect of component (d). The number of contacts between component (d) and component (c) is determined by the ratio of the content of component (c) to the content of component (d). From the viewpoint of increasing the effect of component (d) while not lowering the proportion of component (c) too much, the ratio of the content of component (d) to the content of component (c) is preferably 0.1 or more and 10 or less, more preferably 1 or more and 8 or less, and even more preferably 2 or more and 7 or less.
[0107] The content of component (d) can be measured using X-ray fluorescence spectrometry (XRF). XRF can be performed according to the conditions described in the Examples. XRF determines the content of various metal elements in terms of oxides. For Cu, the content of Cu in terms of CuO is taken as the content of Cu in terms of oxides.
[0108] When the catalyst composition of the present invention contains component (d), it is preferable that components (a) to (d) form a mixture. The mixture of components (a) to (d) is, for example, a mixed particle containing particles of component (a), particles of component (b), particles of component (c), and particles of component (d). Components (a) and (b) may form a complex. The meaning of "complex" is as described above.
[0109] The specific surface area of the catalyst composition of the present invention is preferably 7.0 m 2 / g or more, more preferably 15.0m 2 / g or more, and even more preferably 30.0m 2 / g or more. This allows the catalyst composition of the present invention to have sufficient catalytic active sites for the FT reaction and the RWGS reaction. The upper limit of the specific surface area is not particularly limited, but is, for example, 200.0 m 2 / g or less. This upper limit value may be combined with any of the above-mentioned lower limits. The above-mentioned range of specific surface area is the range of specific surface area before the catalyst composition of the present invention is used for the desired reaction.
[0110] The median diameter D of the catalyst composition of the present invention 50 is preferably 1.0 μm or more, more preferably 2.0 μm or more, and even more preferably 5.0 μm or more, from the viewpoint of increasing the specific surface area of the catalyst composition (i.e., the reaction active points of the catalyst composition). Assuming that the shape of the particles constituting the catalyst composition is a perfect sphere, there is a negative correlation between the particle diameter of the particles constituting the catalyst composition and the specific surface area of the catalyst composition, so that the smaller the particle diameter of the particles constituting the catalyst composition, the larger the specific surface area of the catalyst composition. In other words, the smaller the particle diameter of the particles constituting the catalyst composition, the more reaction active points the catalyst composition has. The median diameter D of the catalyst composition of the present invention 50The upper limit is not particularly limited, but from the viewpoint of improving the handleability during preparation of the catalyst composition, it is preferably 100.0 μm or less, more preferably 70.0 μm or less, and even more preferably 50.0 μm or less. Each of these upper limits may be combined with any of the above-mentioned lower limits.
[0111] Median diameter D 50 The median diameter D of the catalyst composition of the present invention is as described above. 50 can be measured after dispersing the catalyst composition in water, using a particle size distribution measuring device according to the conditions described in the Examples.
[0112] <Method for producing hydrocarbons> The process for producing hydrocarbons according to the present invention will now be described.
[0113] The method for producing hydrocarbons of the present invention includes the production method according to the first embodiment and the production method according to the second embodiment.
[0114] <First aspect> The production method according to the first embodiment includes a step of producing hydrocarbons by contacting CO gas with H2 gas in the presence of the catalyst composition of the present invention.
[0115] The catalyst composition of the present invention is preferably used in the above-mentioned step after being subjected to a reduction treatment. When the catalyst composition of the present invention is subjected to a reduction treatment, at least a part of the component (a) becomes a metal, and the carbide and / or oxide formed by the reaction of the metal with the raw material gas functions as a catalytically active component. For example, at least a part of the oxide of Fe becomes metallic Fe, and the carbide and / or oxide formed by the reaction of metallic Fe with the raw material gas functions as a catalytically active component. The reduction treatment can be performed, for example, by heat treating the catalyst composition of the present invention in a hydrogen atmosphere at a temperature of 300° C. to 500° C. for 1 hour to 24 hours.
[0116] In the above process, the FT reaction is carried out by contacting CO gas with H2 gas in the presence of the catalyst composition of the present invention, and hydrocarbons are produced. The reaction conditions are not particularly limited as long as the FT reaction can proceed. The molar ratio of H2 gas / CO gas is usually 1 / 1 or more and 3 / 1 or less, preferably 1.5 / 1 or more and 2.5 / 1 or less. The gas supply rate is usually 0.5 L / h or more and 100 L / h or less, preferably 30 L / h or more and 50 L / h or less. The temperature is usually 300°C or more and 400°C or less, preferably 350°C or more and 400°C or less. The pressure is usually 0.5 MPa or more and 5 MPa or less, preferably 2.5 MPa or more and 4.5 MPa or less. The reaction time is usually 1 hour or more and 100 hours or less.
[0117] <Second aspect> The manufacturing method according to the second embodiment includes the steps of: (i) contacting CO gas with H gas in the presence of the catalyst composition of the present invention to produce CO gas; and (ii) contacting the CO gas produced in step (i) with H gas in the presence of the catalyst composition of the present invention to produce hydrocarbons. Includes.
[0118] The catalyst composition of the present invention is preferably used in step (i) after being subjected to a reduction treatment. When the catalyst composition of the present invention is subjected to a reduction treatment, at least a part of the component (a) becomes a metal, and the carbide and / or oxide formed by the reaction of the metal with the raw material gas functions as a catalytically active component. For example, at least a part of the oxide of Fe becomes metallic Fe, and the carbide and / or oxide formed by the reaction of metallic Fe with the raw material gas functions as a catalytically active component. The conditions of the reduction treatment are the same as those of the first embodiment.
[0119] In step (i), the RWGS reaction proceeds by contacting CO2 gas with H2 gas in the presence of the catalyst composition of the present invention, and CO gas is produced from CO2 gas. The conditions for contacting CO2 gas with H2 gas are not particularly limited as long as the RWGS reaction can proceed. The molar ratio of H2 gas / CO2 gas is usually 1 / 1 to 5 / 1, preferably 2.5 / 1 to 3.5 / 1. The gas flow rate is usually 0.5 L / h to 100 L / h, preferably 5 L / h to 50 L / h. The temperature is usually 300°C to 400°C, preferably 350°C to 400°C. The pressure is usually 1 MPa to 5 MPa, preferably 2 MPa to 4 MPa. The treatment time is usually 1.5 hours to 100 hours, preferably 1.5 hours to 50 hours.
[0120] In step (ii), the CO gas produced in step (i) is contacted with H2 gas in the presence of the catalyst composition of the present invention, whereby the FT reaction proceeds and hydrocarbons are produced. The conditions for contacting the CO gas and H2 gas are not particularly limited as long as the FT reaction can proceed. The specific conditions are the same as those in the production method according to the first embodiment. The FT reaction and the RWGS reaction may be carried out in the same reactor or in separate reactors.
[0121] Examples of hydrocarbons produced by the production method according to the first or second embodiment include methane, ethane, propane, pentane, and hexane.
[0122] <Method for producing catalyst composition> The catalyst composition of the present invention can be produced, for example, by a precipitation method including the following steps 1 to 4.
[0123] <Process 1> Step 1 is a step of preparing an alkaline aqueous solution (A), a raw material liquid (B), and a raw material liquid (C).
[0124] The alkaline aqueous solution (A) can be prepared, for example, by dissolving a base in water and then adjusting the pH of the resulting aqueous solution, if necessary.
[0125] The base used in the preparation of the alkaline aqueous solution (A) is not particularly limited as long as it dissolves in water or reacts with water to generate hydroxide ions, and can be selected from, for example, carbonates, hydrogen carbonates, hydroxides, ammonium salts, etc. One type of base may be used alone, or two or more types of bases may be used in combination.
[0126] The carbonate can be selected from, for example, alkali metal salts such as sodium carbonate and potassium carbonate, and ammonium salts such as ammonium carbonate and ammonium hydrogen carbonate. One type of carbonate may be used alone, or two or more types of carbonates may be used in combination.
[0127] The hydrogen carbonate may be selected from, for example, alkali metal salts such as sodium hydrogen carbonate and potassium hydrogen carbonate, ammonium hydrogen carbonate, etc. One type of hydrogen carbonate may be used alone, or two or more types of hydrogen carbonate may be used in combination.
[0128] The hydroxide can be selected from alkali metal salts such as sodium hydroxide, potassium hydroxide, etc. One type of hydroxide may be used alone, or two or more types of hydroxides may be used in combination.
[0129] From the viewpoint of promoting the formation of a precipitate, the pH of the alkaline aqueous solution (A) is preferably 9 or more, more preferably 10 or more, and even more preferably 12 or more. The upper limit is not particularly limited. The pH of the alkaline aqueous solution (A) may be, for example, 14 or less. This upper limit may be combined with any of the above-mentioned lower limits.
[0130] If the pH of the aqueous solution obtained by dissolving a base in water is within a predetermined range, it can be used as the alkaline aqueous solution (A) as it is, and if the pH is outside the predetermined range, it can be used as the alkaline aqueous solution (A) after adjusting the pH to within the predetermined range using an acid. The acid used to adjust the pH can be selected from, for example, nitric acid, hydrochloric acid, hydrobromic acid, sulfuric acid, phosphoric acid, etc.
[0131] The raw material liquid (B) contains a raw material for the component (a) and a raw material for the component (b).
[0132] The raw material liquid (B) can be prepared by dissolving or dispersing the raw materials of component (a) and component (b) in water, and then adjusting the pH of the resulting aqueous solution or dispersion, if necessary.
[0133] As the raw material of component (a), for example, one or more selected from water-soluble salts of Group 8 elements, water-soluble salts of Group 9 elements, and water-soluble salts of Group 10 elements can be used. The water-soluble salt can be selected from, for example, nitrates, chlorides, acetates, carbonates, etc., depending on the type of metal element. When component (a) contains Fe, for example, water-soluble Fe salts such as iron nitrate, iron chloride, and iron acetate can be used as the raw material of component (a).
[0134] The raw material for component (b) may be, for example, one or more selected from oxides and hydrates thereof of Group 3 elements, oxides and hydrates thereof of Group 4 elements, oxides and hydrates thereof of Group 5 elements, oxides and hydrates thereof of Group 6 elements, oxides and hydrates thereof of Group 13 elements, and oxides and hydrates thereof of Group 14 elements. When component (b) contains Al, the raw material for component (b) may be, for example, one or two selected from Al oxides and hydrates thereof.
[0135] From the viewpoint of realizing a desired crystallite size of component (b), the Al oxide used as a raw material of component (b) is preferably selected from γ-Al2O3 and θ-Al2O3.
[0136] From the viewpoint of achieving a desired crystallite size of component (b), the hydrate of Al oxide used as a raw material of component (b) is preferably alumina monohydrate, more preferably boehmite.
[0137] The water-soluble salt used in the preparation of the raw material liquid (B) may be a salt whose aqueous solution is neutral, but is preferably a salt whose aqueous solution is acidic. Examples of water-soluble Fe salts whose aqueous solutions are acidic include iron nitrate, iron chloride, and iron acetate.
[0138] The pH of the raw material liquid (B) is not particularly limited as long as a precipitate can be formed by mixing the alkaline aqueous solution (A) and the raw material liquid (B), but is preferably 7 or less, more preferably 4 or less, and even more preferably 3 or less. The lower limit is not particularly limited. The pH of the raw material liquid (B) may be, for example, 1 or more, or 2 or more. Each of these lower limits may be combined with any of the above-mentioned upper limits.
[0139] If the pH of the aqueous solution or dispersion obtained by dissolving or dispersing the raw materials of component (a) and component (b) in water is within a predetermined range, it can be used as raw material liquid (B) as it is, and if the pH is outside the predetermined range, it can be used as raw material liquid (B) after adjusting the pH to within the predetermined range using an acid. The acid used to adjust the pH can be selected from, for example, nitric acid, sulfuric acid, hydrochloric acid, phosphoric acid, etc.
[0140] The raw material liquid (C) contains a raw material of the component (c). The raw material liquid (C) may contain a component (d).
[0141] The raw material liquid (C) can be prepared by dissolving the raw materials of component (c) and, optionally, component (d) in water.
[0142] As the raw material of component (c), for example, one or more selected from water-soluble salts of Group 1 elements and water-soluble salts of Group 2 elements can be used. The water-soluble salt can be selected from, for example, nitrates, chlorides, acetates, carbonates, etc., depending on the type of metal element. When component (c) contains Na, for example, water-soluble Na salts such as sodium nitrate, sodium chloride, sodium acetate, etc. can be used as the raw material of component (c).
[0143] As the raw material of component (d), for example, one or more water-soluble salts of Group 11 elements can be used. The water-soluble salts can be selected from, for example, nitrates, chlorides, acetates, carbonates, etc. When component (d) contains Cu, for example, water-soluble Cu salts such as copper nitrate, copper chloride, copper acetate, etc. can be used as the raw material of component (d). When component (d) contains Ag, for example, water-soluble Ag salts such as silver nitrate, silver chloride, silver acetate, etc. can be used as the raw material of component (d).
[0144] The alkaline aqueous solution (A) and the raw material solutions (B) and (C) may each contain one or more solvents other than water. The one or more solvents other than water can be selected from organic solvents such as alcohol. The total content of the one or more solvents other than water is usually 30 vol% or less, preferably 10 vol% or less, based on the volume of each of the alkaline aqueous solution and the raw material solution. The lower limit is zero.
[0145] <Process 2> Step 2 is a step of mixing the alkaline aqueous solution (A) and the raw material liquid (B).
[0146] When the alkaline aqueous solution (A) and the raw material liquid (B) are mixed, various metal ions contained in the raw material liquid (B) react with one or more selected from hydroxide ions, carbonate ions, and bicarbonate ions contained in the alkaline aqueous solution (A), and possibly with one or more other metal ions contained in the raw material liquid (B) to form poorly water-soluble hydroxides, poorly water-soluble carbonates, poorly water-soluble bicarbonates, or poorly water-soluble carbonate hydroxide salts (hereinafter referred to as "poorly water-soluble hydroxides, etc."), which precipitate together with one or more selected from oxides and hydrates thereof of Group 3 elements, oxides and hydrates thereof of Group 4 elements, oxides and hydrates thereof of Group 5 elements, oxides and hydrates thereof of Group 6 elements, oxides and hydrates thereof of Group 13 elements, and oxides and hydrates thereof of Group 14 elements. For example, one type of metal ion M1 contained in the raw material liquid (B) 2+is one or more selected from hydroxide ions, carbonate ions, and bicarbonate ions in the alkaline aqueous solution (A), and optionally another metal ion M2 contained in the raw material liquid (B). 2+ reacts with to form M1(OH)2, M1CO3, [(M1 x M2 1-x )2(OH)2(CO3)](0 < x ≦ 1), etc. The precipitate is one or more selected from poorly water-soluble hydroxides of Group 8 elements, etc., poorly water-soluble hydroxides of Group 9 elements, etc., and poorly water-soluble hydroxides of Group 10 elements, etc., and one or more selected from oxides and hydrates of Group 3 elements, oxides and hydrates of Group 4 elements, oxides and hydrates of Group 5 elements, oxides and hydrates of Group 6 elements, oxides and hydrates of Group 13 elements, and oxides and hydrates of Group 14 elements. The poorly water-soluble hydroxide, etc. is, for example, particulate. Two or more kinds of particles may form composite particles.
[0147] When the raw material liquid (B) contains a water-soluble Fe salt and one or two or more selected from Al oxides and their hydrates and Si oxides and their hydrates, when the alkaline aqueous solution (A) and the raw material liquid (B) are mixed, the Fe ions contained in the raw material liquid (B) react with one or more selected from hydroxide ions, carbonate ions, and bicarbonate ions contained in the alkaline aqueous solution (A) to form a poorly water-soluble hydroxide (iron hydroxide), a poorly water-soluble carbonate (iron carbonate), a poorly water-soluble bicarbonate (iron bicarbonate), or a poorly water-soluble carbonate hydroxide salt (iron carbonate hydroxide), and precipitate together with one or two or more selected from Al oxides and their hydrates and Si oxides and their hydrates.
[0148] From the viewpoint of adjusting the precipitation rate of the precipitate and / or adjusting the particle size of the precipitate, the pH of the mixed solution of the alkaline aqueous solution (A) and the raw material liquid (B) is preferably 4 or more and 14 or less, more preferably 6 or more and 10 or less. The pH of the mixed solution means the pH of the mixed solution immediately after mixing. The pH of the mixed solution may increase with the passage of time.
[0149] When the alkaline aqueous solution (A) and the raw material liquid (B) are mixed, the raw material liquid (B) may be added to the alkaline aqueous solution (A), or the alkaline aqueous solution (A) may be added to the raw material liquid (B).
[0150] From the viewpoint of making the pH of the entire mixed solution uniform, when mixing the alkaline aqueous solution (A) and the raw material liquid (B), it is preferable to drop one into the other while stirring the other.
[0151] From the viewpoint of safety, the temperature of the alkaline aqueous solution (A) when mixed with the raw material liquid (B) is preferably 20°C or more and 90°C or less, more preferably 20°C or more and 70°C or less, and even more preferably 20°C or more and 60°C or less.
[0152] From the viewpoint of uniformly producing a precipitate, the temperature of the raw material liquid (B) when mixed with the alkaline aqueous solution (A) is preferably 40°C or more and 90°C or less, more preferably 50°C or more and 80°C or less, and even more preferably 60°C or more and 70°C or less.
[0153] From the viewpoint of uniformly forming the precipitate, it is preferable to age the precipitate while stirring the mixture of the alkaline aqueous solution (A) and the raw material liquid (B). The ageing time is preferably 30 minutes to 5 hours, more preferably 30 minutes to 3 hours, and even more preferably 30 minutes to 2 hours. The ageing temperature is preferably 40°C to 90°C, more preferably 50°C to 80°C, and even more preferably 60°C to 70°C.
[0154] The amounts of the alkaline aqueous solution (A) and the raw material liquid (B), the concentration of metal ions contained in the raw material liquid (B), etc. can be appropriately adjusted depending on the composition of the catalyst composition to be produced, etc.
[0155] The precipitate obtained by mixing the alkaline aqueous solution (A) and the raw material liquid (B) is preferably washed with a washing liquid before being subjected to the next step. Water can be used as the washing liquid. The precipitate can be washed by contacting the precipitate with the washing liquid (for example, by mixing the precipitate with the washing liquid). After contacting the precipitate with the washing liquid, solid-liquid separation is performed to obtain the washed precipitate in the form of a cake. The solid-liquid separation method can be selected from, for example, filtration, centrifugation, decantation, etc. The precipitate is preferably washed until the amount of metal elements (e.g., alkali metal elements such as Na, K, etc.) derived from the alkaline aqueous solution (A) contained in the filtrate or supernatant obtained by solid-liquid separation after contacting the precipitate with the washing liquid becomes 100 ppm or less (particularly 5 ppm or less).
[0156] The precipitate obtained by mixing the alkaline aqueous solution (A) and the raw material liquid (B) is preferably formed into a cake and dried before being subjected to the next step. When washing the precipitate, it is preferable to form the precipitate after washing into a cake and dry the cake. The drying can be carried out according to a conventional method. The drying temperature is usually 60°C or higher and 150°C or lower, preferably 100°C or higher and 120°C or lower, and the drying time is usually 3 hours or higher and 24 hours or lower, preferably 5 hours or higher and 12 hours or lower.
[0157] The dried cake may be pulverized as necessary. The pulverization can be carried out according to a conventional method. For example, the pulverization can be carried out in a dry or wet manner using a mortar, a hammer mill, a ball mill, a bead mill, a jet mill, a roller mill, or the like.
[0158] <Process 3> Step 3 is a step of calcining the precipitate obtained in step 2. Note that step 3 can be omitted.
[0159] The precipitate can be calcined according to a conventional method. Calcination is usually carried out in an air atmosphere. The calcination temperature is usually 300° C. or higher and 500° C. or lower, preferably 350° C. or higher and 450° C. or lower. The calcination time is usually 2 hours or higher and 5 hours or lower, preferably 3 hours or higher and 4 hours or lower.
[0160] The calcined precipitate may be pulverized as necessary. The pulverization may be carried out according to a conventional method. For example, the pulverization may be carried out in a dry or wet manner using a mortar, a hammer mill, a ball mill, a bead mill, a jet mill, a roller mill, or the like.
[0161] By calcining the precipitate, a mixture or a composite of component (a) and component (b) is obtained. When the precipitate contains one or more selected from poorly water-soluble hydroxides of Group 8 elements, poorly water-soluble hydroxides of Group 9 elements, and poorly water-soluble hydroxides of Group 10 elements, at least a part of the poorly water-soluble hydroxides is converted to an oxide by calcining the precipitate. When the precipitate contains one or more selected from hydrates of oxides of Group 3 elements, hydrates of oxides of Group 4 elements, hydrates of oxides of Group 5 elements, hydrates of oxides of Group 6 elements, hydrates of oxides of Group 13 elements, and hydrates of oxides of Group 14 elements, at least a part of the hydrates is converted to an oxide by calcining the precipitate. For example, when the precipitate contains Fe hydroxide, at least a part of the Fe hydroxide is converted to Fe oxide by calcining the precipitate. When the precipitate contains Al oxide hydrate, at least a part of the Al oxide hydrate is converted to Al oxide by calcining the precipitate. When the Al oxide hydrate is boehmite, at least a part of the boehmite becomes Al2O3 by firing the precipitate. The Al2O3 generated from the boehmite is, for example, one or more selected from α-Al2O3, γ-Al2O3, and θ-Al2O3. The Al2O3 generated from the boehmite usually contains γ-Al2O3. A part of the boehmite may remain as boehmite even after firing.
[0162] <Step 4> Step 4 is a step of impregnating the precipitate obtained in step 2 or the mixture or composite obtained in step 3 with the raw material liquid (C) and then calcining the same.
[0163] Step 4 can be carried out, for example, as follows. The precipitate obtained in step 2 or the mixture or composite obtained in step 3 is added to the raw material liquid (C) and stirred, and the obtained dispersion is dried and heated to obtain a powder. The obtained powder is dried and the dried powder is fired. The drying and firing can be carried out according to a conventional method. The drying temperature is usually 50°C or higher and 120°C or lower, preferably 60°C or higher and 80°C or lower, and the drying time is usually 2 hours or higher and 24 hours or lower, preferably 3 hours or higher and 12 hours or lower. The firing is usually carried out in an air atmosphere. The firing temperature is usually 300°C or higher and 500°C or lower, preferably 350°C or higher and 450°C or lower. The firing time is usually 2 hours or higher and 5 hours or lower, preferably 3 hours or higher and 4 hours or lower. When a nitrate is used as a raw material for components (c) and / or (d), at least a part of the nitrate may remain in the form of a nitrate (nitrate oxide).
[0164] In step 4, component (c) can be supported on the precipitate obtained in step 2 or the mixture or composite obtained in step 3. When the raw material liquid (C) contains a raw material for component (d) in addition to the raw material for component (c), components (c) and (d) can be supported on the precipitate obtained in step 2 or the mixture or composite obtained in step 3 in step 4. In this manner, the catalyst composition of the present invention can be obtained. EXAMPLES
[0165] [Example 1] (1) Preparation of a mixture of Al oxide and Fe oxide A mixture of Al oxide and Fe oxide was prepared using a precipitation method. Specifically, the process is as follows. 76.6 g of iron (III) nitrate nonahydrate and 8.2 g of a 17% by mass boehmite dispersion were added to 268 g of pure water and stirred to obtain a raw material liquid (B). The boehmite dispersion was obtained by dispersing boehmite (α-AlOOH) in an acidic solution. The obtained raw material liquid (B) was heated to 70°C, and then sodium hydroxide aqueous solution (A) was dropped therein until the pH reached 6.7, forming a precipitate. The precipitate was then aged while the mixture of sodium hydroxide aqueous solution (A) and raw material liquid (B) was stirred at 70°C for 30 minutes to obtain a suspension. The obtained suspension was filtered by suction to recover the precipitate, and the precipitate was dispersed in pure water and the obtained dispersion was filtered by suction, and the precipitate was washed by repeating this process. The washing was repeated until the Na concentration of the filtrate was 2 ppm or less. The Na concentration was measured using an ion concentration meter (LAQUAtwin-Na-11, manufactured by Horiba, Ltd.). The washed precipitate was dried overnight in a drying chamber (air atmosphere) at 100°C. The dried precipitate was calcined at 400°C for 4 hours to obtain a mixture of Al oxide and Fe oxide. At least a part of the boehmite becomes γ-Al2O3 by calcination. Some of the boehmite may remain as boehmite even after calcination. The fact that at least a part of the boehmite has become γ-Al2O3 can be confirmed by the presence or absence of a peak derived from γ-Al2O3 in the X-ray diffraction pattern of the catalyst composition.
[0166] (2) Sodium oxide loading process Using the impregnation support method, Na oxide was supported on the mixture of Al oxide and Fe oxide. Specifically, it is as follows. 0.11 g of sodium nitrate was dissolved in 50 g of pure water to prepare raw material liquid (C). 3 g of a mixture of Al oxide and Fe oxide was added to the raw material liquid (C) and stirred to obtain a dispersion liquid. The obtained dispersion liquid was reduced in pressure to 70 Pa using an evaporator and heated to 60 ° C. using a water bath to obtain a powder. The obtained powder was dried overnight in a drying chamber (air atmosphere) at 100 ° C. The dried powder was calcined at 400 ° C. for 3 hours to support Na oxide on the mixture of Al oxide and Fe oxide, and the catalyst composition of Example 1 was obtained. The charging values of the raw materials are shown in Table 1. The charging values are values calculated assuming that each raw material exists as an oxide.
[0167] [Example 2] Except for changing the amount of sodium nitrate used to 0.22 g, a mixture of Al oxide and Fe oxide was obtained in the same manner as in Example 1, and Na oxide was supported on the obtained mixture to obtain a catalyst composition of Example 2. The amounts of the raw materials charged are shown in Table 1.
[0168] [Example 3] Except for changing the amount of sodium nitrate used to 0.59 g, a mixture of Al oxide and Fe oxide was obtained in the same manner as in Example 1, and Na oxide was supported on the obtained mixture to obtain a catalyst composition of Example 3. The amounts of the raw materials charged are shown in Table 1.
[0169] [Example 4] Except for changing the amount of the boehmite dispersion to 2.0 g and the amount of sodium nitrate to 0.22 g, a mixture of Al oxide and Fe oxide was obtained in the same manner as in Example 1, and Na oxide was supported on the obtained mixture to obtain a catalyst composition of Example 4. The amounts of the raw materials charged are shown in Table 1.
[0170] [Example 5] A mixture of Al oxide and Fe oxide was obtained in the same manner as in Example 1, except that the amount of the boehmite dispersion was changed to 21.8 g and the amount of sodium nitrate was changed to 0.22 g, and Na oxide was supported on the obtained mixture to obtain a catalyst composition of Example 5. The amounts of the raw materials charged are shown in Table 1.
[0171] [Example 6] A mixture of γ-alumina and Fe oxide was obtained in the same manner as in Example 1, except that the amount of sodium nitrate was changed to 0.22 g and 2.4 g of γ-alumina (γ-Al2O3) was used instead of the boehmite dispersion, and Na oxide was supported on the obtained mixture to obtain the catalyst composition of Example 6. The amounts of the raw materials charged are shown in Table 1.
[0172] [Example 7] A mixture of θ-alumina and Fe oxide was obtained in the same manner as in Example 1, except that the amount of sodium nitrate was changed to 0.22 g and 2.4 g of θ-alumina (θ-Al2O3) was used instead of the boehmite dispersion, and Na oxide was supported on the obtained mixture to obtain a catalyst composition of Example 7. The amounts of the raw materials charged are shown in Table 1.
[0173] [Example 8] A mixture of θ-alumina and Fe oxide was obtained in the same manner as in Example 1, except that 0.23 g of sodium nitrate and 0.40 g of copper (II) nitrate trihydrate were dissolved in 50 g of pure water to prepare raw material solution (C), 2.4 g of θ-alumina (θ-Al2O3) was used instead of the boehmite dispersion, and the calcination of the precipitate after drying in the preparation step of the mixture of Al oxide and Fe oxide was omitted, and Na oxide and Cu oxide were supported on the obtained mixture to obtain the catalyst composition of Example 8. The charging amounts of the raw materials are shown in Table 1.
[0174] [Example 9] A mixture of θ-alumina and Fe oxide was obtained in the same manner as in Example 1, except that 0.15 g of sodium nitrate and 0.37 g of silver nitrate were dissolved in 50 g of pure water to prepare raw material solution (C), 2.4 g of θ-alumina (θ-Al2O3) was used instead of the boehmite dispersion, and the firing of the precipitate after drying in the preparation step of the mixture of Al oxide and Fe oxide was omitted, and Na oxide and Ag oxide were supported on the obtained mixture to obtain the catalyst composition of Example 9. The charging amounts of the raw materials are shown in Table 1.
[0175] [Comparative Example 1] Except for changing the amount of sodium nitrate to 0.22 g and using 8.9 g of aluminum nitrate (III) nonahydrate instead of the boehmite dispersion, a composite oxide of Al and Fe was obtained in the same manner as in Example 1, and Na oxide was supported on the obtained composite oxide to obtain a catalyst composition of Comparative Example 1. The amounts of the raw materials charged are shown in Table 1.
[0176] [Comparative Example 2] Except for changing the amount of sodium nitrate to 0.22 g and using 2.4 g of α-alumina instead of the boehmite dispersion, a mixture of α-alumina and Fe oxide was obtained in the same manner as in Example 1, and Na oxide was supported on the obtained mixture to obtain a catalyst composition of Comparative Example 2. The amounts of the raw materials charged are shown in Table 1.
[0177] [Comparative Example 3] Except for changing the amount of sodium nitrate used to 0.22 g and not using the boehmite dispersion liquid, Fe oxide was obtained in the same manner as in Example 1, and Na oxide was supported on the obtained Fe oxide to obtain a catalyst composition of Comparative Example 3. The amounts of raw materials charged are shown in Table 1.
[0178] [Comparative Example 4] Except for not using the boehmite dispersion liquid and not carrying out the Na oxide supporting step, Fe oxide was obtained in the same manner as in Example 1, and this was used as the catalyst composition of Comparative Example 4. The amounts of the raw materials charged are shown in Table 1.
[0179] [Comparative Example 5] Except for using 2.4 g of aluminum nitrate (III) nonahydrate instead of the boehmite dispersion and not carrying out the Na oxide supporting step, a composite oxide of Al and Fe was obtained in the same manner as in Example 1, and this was used as the catalyst composition of Comparative Example 5. The amounts of the raw materials charged are shown in Table 1.
[0180] [Comparative Example 6] Except for not carrying out the Na oxide supporting step, a composite of Al oxide and Fe oxide was obtained in the same manner as in Example 1, and this was used as the catalyst composition of Comparative Example 5. The amounts of the raw materials charged are shown in Table 1.
[0181] [Test example] (1) Composition analysis The composition of the samples obtained from each catalyst composition was evaluated using XRF (Rigaku Corporation, Primus II). The conditions of X-ray excitation, 2θ scan, and optical system (attenuator, slit, analyzing crystal, detector) during measurement were as follows, with the measurement diameter of 10 mm, the qualitative range F to U, and the measurement time standard. Semi-quantitative composition analysis was performed by the FP method using the SQX software built into the device for the measurement results. The composition was calculated assuming that each metal element exists as an oxide. The XRF measurement values of each catalyst composition are shown in Table 1.
[0182] [XRF measurement conditions] X-ray source: Rh kα, voltage: 50 kV, current: 50 mA, attenuator: 1 / 1, slit: S2 (Fe Kα) · S4 (AlKα, NaKα), analyzing crystal: LiF (FeKα) · PET (AlKα) · RX25 (NaKα), detector: SC (FeKα) · PC (AlKα, NaKα), measurement angle: 5-90° (FeKα) · 140-148° (AlKα) · 44.718-50.718° (NaKα), sampling width: 0.02° (FeKα) · 0.05° (AlKα, NaKα), scan speed: 30° / min
[0183] (2) Evaluation of crystallite size X-ray diffraction (XRD) was performed using a sample obtained from each catalyst composition and a commercially available powder X-ray diffractometer (Rigaku Corporation, RINT-TTRIII) to obtain an X-ray diffraction pattern for each catalyst composition. XRD was performed under the following conditions: X-ray source: CuKα, operation axis: 2θ / θ, measurement method: continuous, counting unit: cps, start angle: 5°, end angle: 80°, sampling width: 0.02°, scan speed: 0.1° / min, voltage: 50 kV, current: 300 mA.
[0184] In the X-ray diffraction pattern of each catalyst composition, a peak derived from Fe2O3, a peak derived from α-Al2O3, a peak derived from γ-Al2O3, or a peak derived from θ-Al2O3 was identified, and the Scherrer formula was applied to the identified peaks to calculate the crystallite diameter of Fe2O3, the crystallite diameter of α-Al2O3, the crystallite diameter of γ-Al2O3, or the crystallite diameter of θ-Al2O3. The crystallite diameter obtained from the peak at 2θ = 35.6 ° ± 0.5 ° was taken as the crystallite diameter of Fe2O3, the crystallite diameter obtained from the peak at 2θ = 43.0 ° ± 0.5 ° was taken as the crystallite diameter of α-Al2O3, and the crystallite diameter obtained from the peak at 2θ = 45.0 ° ± 0.5 ° was taken as the crystallite diameter of γ-Al2O3 or θ-Al2O3. The evaluation of the crystallite diameter is shown in Table 2. The Scherrer formula is as follows, and the Scherrer constant was set to 0.94. D=K×λ / Bcosθ [In the formula, D represents the crystallite size (nm), K represents the Scherrer constant, λ represents the wavelength of X-rays (nm), B represents the broadening of the diffraction line width (rad), and θ represents the Bragg angle (rad).]
[0185] In Examples 1 to 9 and Comparative Examples 1 to 6, the crystallite diameter of Fe2O3 was taken as the crystallite diameter of component (a). In Examples 1 to 3, Examples 5 to 6 and Comparative Example 6, the crystallite diameter of γ-Al2O3 was taken as the crystallite diameter of component (b), in Examples 7 to 9, the crystallite diameter of θ-Al2O3 was taken as the crystallite diameter of component (b), and in Comparative Example 2, the crystallite diameter of α-Al2O3 was taken as the crystallite diameter of component (b). In Comparative Examples 1 and 5 in which composite oxides of Al and Fe were obtained, the crystallite diameter was obtained from the peak present at 2θ=36.1±0.5°. The crystallite diameter of the composite oxide is shown in Table 2 as the crystallite diameter of component (a), and the crystallite diameter of component (b) is shown as "-". In Example 4, the amount of boehmite used was small, and the peak of γ-Al2O3 was not detected, so the crystallite diameter of component (b) in Example 4 was shown as "ND" (Not Detected).
[0186] (3) Median diameter D 50 Evaluation A laser diffraction / scattering particle size distribution measuring device (BECKMAN COULTER, LS 13 320) was used to measure the particle size distribution of each catalyst composition and the particle size distribution of the raw material of component (b) (boehmite in Examples 1 to 5 and Comparative Example 6, γ-alumina in Example 6, θ-alumina in Examples 7 to 9, and α-alumina in Comparative Example 2). LS 13 320 version 6.01 was used as the measurement software. The particle size distribution was measured as follows. 0.05 g of the catalyst composition or the raw material of component (b) was placed in 5 mL of ion-exchanged water and stirred. Thereafter, the dispersion was introduced into the device, and the ultrasonic output was set to 8 using the ultrasonic kit for universal liquid module (BECKMAN COULTER, Sonication Control Unit) attached to the device. After irradiating with ultrasonic waves for 3 minutes, the median diameter D 50 (The cumulative particle size D at which the cumulative volume reaches 50% in the volume-based particle size distribution) 50 ) was measured. 50 When measuring the refractive index, 2.9, which is the value for Fe2O3, was used. When measuring the raw material of component (b), 1.8, which is the value for Al2O3, was used. The measurement results are shown in Table 2. Note that the D of the raw material of component (b) in Comparative Examples 1 and 5 was 50Since aluminum nitrate (III) nonahydrate dissolved in ion-exchanged water, making measurement difficult, the result was recorded as "ND" (Not Detected).
[0187] (4) Measurement of specific surface area The samples obtained from each catalyst composition were heat-treated at 120°C for 10 minutes in an air atmosphere, and then the specific surface area was measured. The specific surface area was measured by the BET single-point method using a commercially available BET specific surface area measuring device (Microtrack-Bell Corporation, BELSORP MR6). The BET single-point method was performed according to "(3.5) Single-point method" in "6.2 Flow method" of JIS R1626:1996 "Method for measuring the specific surface area of fine ceramic powders by gas adsorption BET method". As the gas, a nitrogen-helium mixed gas containing 30% by volume of nitrogen as an adsorption gas and 70% by volume of helium as a carrier gas was used, and single-point measurement was performed within the range of equilibrium relative pressure of 0.05 to 0.35. The measurement results of the specific surface area are shown in Table 3. The specific surface area was measured before and after "(6) Catalytic activity test for reactions using CO2 and H2 as raw gases" described later.
[0188] (5) Catalytic activity test for reactions using CO and H2 as raw gas A catalytic activity test was carried out on the sample obtained from the catalyst composition of Example 2 as follows. As a pretreatment, 1 cc of the sample was filled in a reaction tube and heat-treated at 400°C for 2 hours under a pure H2 gas atmosphere, and the temperature inside the reactor was lowered to room temperature (25°C). The reaction tube was made of SUS316 and had an inner diameter of 10.22 mm. After the temperature was lowered, a catalytic activity test was carried out by passing gas through the reaction tube. At this time, the gas composition was H2 / CO=2, the total pressure was 3 MPa, the gas rate was 5 L / h, the temperature was 380°C, and the treatment time was 1.5 hours. The online gas at the outlet of the reaction tube was quantified by GC-FID (Gas Chromatography-Flame Ionization Detector) to determine the CO conversion rate. The CO conversion rate was 98.8%. The CO conversion rate was calculated using the following formula. CO conversion rate (%) = [(flow rate of CO in the supply gas - flow rate of CO in the exhaust gas) / number of moles of CO in the supply gas] x 100%
[0189] (6) Catalytic activity tests for reactions using CO2 and H2 as raw gases A catalytic activity test was carried out on the samples obtained from each catalyst composition as follows. As a pretreatment, 1 cc of the sample was filled into the reaction tube, and heat-treated at 400°C for 2 hours under a pure H2 gas atmosphere, and the temperature inside the reactor was lowered to room temperature (25°C). The reaction tube was made of SUS316 and had an inner diameter of 10.22 mm. After lowering the temperature, a catalytic activity test was carried out by passing gas through the reaction tube. At this time, the gas composition was H2 / CO2=3, the total pressure was 3 MPa, the gas rate was 40 L / h, the temperature was 380°C, and the treatment time was 1.5 hours. The online gas at the outlet of the reaction tube was quantified using a GC-FID (Gas Chromatography-Flame Ionization Detector) to determine the CO2 conversion rate. The CO2 conversion rates are shown in Table 3. The CO2 conversion rate was calculated using the following formula. CO2 conversion rate (%) = [(CO2 flow rate in supply gas - CO2 flow rate in exhaust gas) / CO2 flow rate in supply gas] x 100%
[0190] [Table 1]
[0191] [Table 2]
[0192] [Table 3]
[0193] As is clear from Table 3, the catalyst compositions of Examples 1 to 9 had a low specific surface area reduction rate before and after the catalytic activity test. The catalyst compositions of Comparative Examples 1 and 6 had a low specific surface area reduction rate, but a low CO2 conversion rate, and were insufficient in catalytic performance compared to the catalyst compositions of Examples 1 to 9.
Claims
1. 1. A catalyst composition for catalyzing a Fischer-Tropsch reaction, comprising: Ingredients below: (a) one or more components selected from oxides of Group 8 elements, oxides of Group 9 elements, and oxides of Group 10 elements; (b) one or more components selected from oxides and hydrates thereof of Group 3 elements, oxides and hydrates thereof of Group 4 elements, oxides and hydrates thereof of Group 5 elements, oxides and hydrates thereof of Group 6 elements, oxides and hydrates thereof of Group 13 elements, and oxides and hydrates thereof of Group 14 elements; and (c) one or more components selected from the group consisting of oxides, carbonates, and nitrates of Group 1 elements and oxides, carbonates, and nitrates of Group 2 elements; Including, A catalyst composition, wherein the crystallite size of the component (b) is 5.0 nm or more and 90.0 nm or less.
2. The catalyst composition of claim 1 which catalyzes the reverse water gas shift reaction.
3. 3. The catalyst composition according to claim 1, wherein the crystallite size of the component (a) is 200.0 nm or less.
4. The catalyst composition according to claim 1 or 2, wherein the content of the component (b) is from 1.0 mass % to 50.0 mass % based on the mass of the catalyst composition.
5. 3. The catalyst composition according to claim 1, wherein the content of the component (a) is from 30.0 mass % to 98.0 mass % based on the mass of the catalyst composition.
6. 3. The catalyst composition according to claim 1, wherein the content of the component (c) is 0.1 mass% or more, based on the mass of the catalyst composition.
7. 3. The catalyst composition according to claim 1 or 2, wherein the component (b) comprises one or more elements selected from Al, Zr and Si.
8. The component (b) is boehmite, γ-Al 2 O 3 and θ-Al 2 O 3 The catalyst composition according to claim 1 or 2, comprising one or more selected from the following:
Citation Information
Patent Citations
Production of lower olefins from synthesis gas
JP2013509353A
JP24786A